The WPA guide to Kentucky - Simon, F. Kevin, 1952- (The University Press of Kentucky, 2015)
One of the first great reference tools on the Commonwealth, this WPA Guide is an important, vital part of our heritage. While it includes brief essays describing Kentucky's history, folklore, education, industry, geology, ethnic mix and other topics, the most remarkable feature is the driving tours that are as accurate today as they were more than half a century ago. Careful annotations give directions, point out historical and tourist sites, describe the country side, and even provide mileage for the drives.